Intellectual Property Rights and Royalties in Franchise Business Taxation - Evelyne Shafina; Tri Ameliyaningsih; Indra Pahala; Puji Wahono (Transpublika Publisher, 2025)
Intellectual Property Rights (IPR) are rights that are born from human thought, producing useful products or processes. IPR gives the right to obtain economic benefits from creativity. This study aims to understand the concept of IPR and royalty in franchise business tax, with a normative juridical approach and literature analysis to review the applicable rules. In the franchise business, royalties, engineering services, and business income are the objects of Income Tax. IPR protection includes trademark, patent, and copyright rights. Franchise taxes on royalties help regulate Indonesian legal entities according to Tax Law Number 7 of 2008. The law specifies conditions and tax rates for different businesses. Corporate taxpayers face a 25% tax rate, while domestic corporations on the stock exchange with at least 40% shares traded pay 20%. Companies with a gross turnover under Rp4,800,000,000 pay a 1% tax rate.